Analisis Alur Manajemen Transportasi dalam Meningkatkan Efisiensi Pengiriman di Gudang PT Xpresindo Logistik Utama Medan - Baihaqi Ahmad; Indra Suganda Tampubolon; Rizky Hayyuda; Shelvia Putri Ananda; Artha Putri Br. Karo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the transportation management flow at PT Xpresindo Logistik Utama Medan Warehouse and its impact on delivery accuracy. The research method used a qualitative approach through direct observation and interviews with warehouse managers and operational staff. The results showed that the distribution flow from receiving goods from Jakarta to shipping to customers in Medan was quite effective, although it was still dominated by manual systems such as the use of Delivery Notes and Excel records. The use of the Monstra tracking application was not evenly distributed, so fleet movement information was not always updated in real time, especially when demand volume increased at the end of the month. To improve efficiency, the study recommended the implementation of a Transportation Management System (TMS), digitalization of barcode/QR code-based inventory processes, and a Key Performance Indicator (KPI) dashboard to monitor delivery timeliness and fleet utilization periodically.